Stance in Advanced Academic Writing by Saudi EFL Postgraduates: A Corpus-Based Study of Critique Writing - Abdulwahid Qasem Al Zumor (Journal of Languages and Language Teaching, 2021)
Whether the postgraduate students in the EFL context are adequately trained to express their authorial voice in academic writing in an appropriate tone has not been clarified enough in the literature. The aim of this study is to explore the linguistic resources used by Saudi postgraduate students of Applied Linguistics to construct stance when they write critique essays. To achieve this goal, a corpus of 78000 words was built from 73 critique essays collected in five years. To analyze this corpus, LancsBox corpus analysis software was used to generate the concordances with frequencies of key words in context. The model of corpus analysis used was Hyland’s (2005) which views stance as a construct within a model of interaction in academic discourse that comprises boosters, hedges, attitude markers, and self-mentions. The major findings of the study showed that the most frequently used stance markers were hedges, followed by attitude markers, then boosters, and finally self-mentions. In addition, the linguistic resources used in these strategies of stance construction by the students in this particular context need to be enhanced in order to conform with conventional standards of academic writing. To meet this ambitious requirement, the study recommends explicit instruction, training, and showcasing these textual resources as they occur in high quality discipline-specific publications.